The Influence of Community Understanding in Interest of Transaction in Sharia Banking - Syah, Alam Firman (Universitas Muhammadiyah Surakarta, 2023)
Islamic banking has challenges in society's development. The small number of customers transacting in Islamic banking requires a special study to find solutions to developing public interest in Islamic banking. The purpose of this study is to determine the influence of public understanding of transactions in Islamic banking through various studies that have been conducted. The method used is analytical descriptive research with literature study. 8 (eight) articles are following the research. The study states that there is a relationship between public understanding/literacy and interest in transactions in Islamic banking.